mRNA Expression Of Bone Morphogenetic Protein 7 (bmp7) During Folliculogenesis In Zebrafish - Lim, Phaik Siew (2011)
The potential roles of bone morphogenetic protein 7 (bmp7) in ovary have drawn increasing attention. Present study aims to investigate the expression pattern of bmp7a and bmp7b in zebrafish. Adult female tissues were sacrificed for sampling of brain, eye, gill, heart, intestine, kidney, ovary, liver and swim bladder. For follicle compartments, follicle layers were mechanically separated from oocytes after cold-shock treatment. To verify analysis of bmp7a and bmp7b expression during different follicle stages, previtellogenic; early- and mid-vitellogenic mixed; full-grown immature at daytime, 0300 h, 0400 h; maturation (0500 h) and ovulation (0600 h) stage were isolated from dissected ovaries. Using semi-quantitative real-time PCR, bmp7a was found to be abundantly expressed in ovary whereas bmp7b was highly expressed in swim bladder, brain, eye, gill and ovary. Both molecules were predominantly expressed in the follicle layers rather than the oocyte. During folliculogenesis, bmp7a and bmp7b were expressed highly at previtellogenic stage. Thereafter, bmp7a remained rather constant across follicle developmental stages. In contrast, bmp7b expression progressively reduced to extremely low level at ovulation across the developing follicles. Overall, this finding indicated the possible importance of bmp7b as an autocrine/paracrine growth factor for follicular development at previtellogenic and, as repressor of oocyte maturation during folliculogenesis.